Optimization of Interdigitated Electrodes in Electric Field Distribution and Thermal Effect - Ismail, S.; Mahmood, N. H.; Abdul Razak, M. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Microfluidic is used to separate, transport and manipulate particles through a micro-scale device. This paper presents the numerical simulation of interdigitated electrodes that is commonly used for continuous particle separation using electrical separation microfluidic device which demonstrates dielectrophoretic (DEP) force. The strength of DEP force depends on the gradient of electric field generated by the electrodes. Besides, the effect of Joule heating generated by the electrodes would harm the living particles. The interdigitated electrodes arrays are simulated using COMSOL Multiphysics 3.5. The gradient of electric field distribution and temperature generated are simulated for different width and gap of the electrode. The simulation results are analysed and discussed to determine the best electrode dimension to be fabricated for bio-particles separation application. The optimum interdigitated electrode dimension identified in this research was 60µm:180µm (width:gap) that generate 1.92x1016 V2m-3 of electric field gradient and temperature of 68°C on the electrode surface, and electric field gradient of 1.83x1013 V2m-3 and temperature about 40°C when 80µm above the electrode with the conductivity of the fluid is 1.09 S/m (mimic blood conductivity).